Analgesic Alkaloids Derived From Traditional Chinese Medicine in Pain Management - Jiang, Wei; Tang, Mingze; Yang, Limin; Zhao, Xu; Gao, Jun; Jiao, Yue; Li, Tao; Tie, Cai; Gao, Tianle; Han, Yanxing; Jiang, Jian-Dong (Frontiers in Pharmacology, 2022)
Chronic pain is one of the most prevalent health problems. The establishment of chronic pain is complex. Current medication for chronic pain mainly dependent on anticonvulsants, tricyclic antidepressants and opioidergic drugs. However, they have limited therapeutic efficacy, and some even with severe side effects. We turned our interest into alkaloids separated from traditional Chinese medicine (TCM), that usually act on multiple drug targets. In this article, we introduced the best-studied analgesic alkaloids derived from TCM, including tetrahydropalmatine, aloperine, oxysophocarpine, matrine, sinomenine, ligustrazine, evodiamine, brucine, tetrandrine, Stopholidine, and lappaconitine, focusing on their mechanisms and potential clinical applications. To better describe the mechanism of these alkaloids, we adopted the concept of drug-cloud (dCloud) theory. dCloud illustrated the full therapeutic spectrum of multitarget analgesics with two dimensions, which are “direct efficacy”, including inhibition of ion channels, activating γ-Aminobutyric Acid / opioid receptors, to suppress pain signal directly; and “background efficacy”, including reducing neuronal inflammation / oxidative stress, inhibition of glial cell activation, restoring the balance between excitatory and inhibitory neurotransmission, to cure the root causes of chronic pain. Empirical evidence showed drug combination is beneficial to 30%-50% chronic pain patients. To promote the discovery of effective analgesic combinations, we introduced an ancient Chinese therapeutic regimen that combines herbal drugs with “Jun”, “Chen”, “Zuo”, and “Shi” properties. In dCloud, “Jun” drug acts directly on the major symptom of the disease; “Chen” drug generates major background effects; “Zuo” drug has salutary and supportive functions; and “Shi” drug facilitates drug delivery to the targeted tissue. Subsequently, using this concept, we interpreted the therapeutic effect of established analgesic compositions containing TCM derived analgesic alkaloids, which may contribute to the establishment of an alternative drug discovery model.